Capacidad antagónica de trichoderma spp., a nivel in vitro frente a los hongos fitopatógenos crinipellis perniciosa y moniliopthora roreri. - Párraga Vélez, Johan Reinaldo (2013)
In order to evaluate the potential antagonistic fungus trichoderma spp, against phytopathogenic fungi monilopthora crinipellis roreri permicious, these strains were isolated from samples collected microorganisms clonal cocoa garden located in the field MFL ESPAM